Host tree impact on Lymantria species under CO2 and temperature changes - Barbora Dvořáková; Jaroslav Holuša; David Musiolek; Alina Kalyniukova; Jaromír Hradecký; Jaroslav Čepl; Axel Schopf (Frontiers in Forests and Global Change)
IntroductionClimate change has led to rising atmospheric CO2 levels and temperatures, projected to double CO2 concentrations and increase temperatures by 2–5°C by the end of the 21st century. These environmental changes influence plant primary and secondary metabolism, potentially altering plant-insect interactions. Herbivore performance depends on the nutritional quality of host plants, which may decline with elevated CO2 due to an increased carbon-to-nitrogen (C:N) ratio. To explore these effects, the performance of spongy moth larvae (Lymantria dispar) was assessed on oak (Quercus robur) and spruce (Picea abies) seedlings grown under varying climatic conditions. This approach compares a preferred host with a non-preferred one in the case of L. dispar, providing insight into how host plant selection may be influenced under future climate scenarios. In addition, the nun moth (Lymantria monacha), a conifer-feeding species, was also studied on the experimental spruce seedlings to facilitate a comparison with a specialist herbivore.MethodsThree-year-old oak and spruce seedlings were reared for 1 year under four climate scenarios combining two CO2 levels (ambient: 410 ppm and elevated: 820 ppm) and two temperature regimes (20:15°C and 25:20°C). Seedlings were then processed into leaf powder diets for laboratory bioassays with larvae. Secondary metabolites in the seedlings were analyzed to assess climate-induced changes in tree composition and their effects on herbivores.ResultsElevated CO2 increased the C:N ratio in both tree species, with spruce showing a higher ratio than oak. Higher temperatures led to increased nitrogen content, particularly in oak seedlings. L. dispar performed better on oak despite higher secondary metabolite concentrations, while L. monacha exhibited minimal variation in performance on spruce across climate treatments.ConclusionThe combined effects of elevated CO2 levels and increased temperatures impacted plant quality; however, there were nearly no differences in the performance of Lymantria larvae. Despite the higher concentrations of secondary metabolites in the trees, the larvae were able to thrive effectively, demonstrating their resilience to environmental changes.